Corrigendum to “Modeling Affective Commitment and Job Satisfaction as A Mediating Role in Predicting Turnover Intention among Gen Z Employees” [JBTI: Jurnal Bisnis: Teori dan Implementasi, Vol. 15 No. 2 (2024): August 2024 Page 143-160] - Cakti Indra Gunawan; Nanda Dwi Maharani; Dodi Wirawan Irawanto (Universitas Muhammadiyah Yogyakarta, 2025)
Corrected:Modeling Affective Commitment and Job Satisfaction as A Mediating Role in Predicting Turnover Intention among Gen Z EmployeesCakti Indra Gunawan, Nanda Dwi Maharani, Dodi Wirawan IrawantoAugust 28th, 2024 The author notes that the published version of this article contains a typographical error in the reporting of the number of statement items. On page 148, the text refers to 10 statement items, whereas the correct number, consistent with the original source material from Gyensare et al. (2016) and the analysis presented in Figure 2 (page 150), is 15 statement items. This correction pertains solely to the misrepresentation of the number of items due to a typing error. The correction does not affect the analytical procedures, interpretation, or the overall conclusions of the study. The author regrets this oversight and apologizes for any inconvenience caused. DOI of the original article: https://doi.org/10.18196/jbti.v15i2.20881